Neural Representation of the English Vowel Feature [High]: Evidence From /ε/ vs. /ɪ/ - Yu, Yan H.; Shafer, Valerie L. (Frontiers in Human Neuroscience, 2021)
Many studies have observed modulation of the amplitude of the neural index Mismatch Negativity (MMN) related to which member of a phoneme contrast [phoneme A, phoneme B] serves as the frequent (standard) and which serves as the infrequent (deviant) stimulus (i.e., AAAB versus BBBA) in an oddball paradigm. Explanations for this amplitude modulation range from acoustic to linguistic factors. We tested whether exchanging the role of the mid vowel // versus high vowel /ɪ/ of English modulated MMN amplitude and whether the pattern of modulation was compatible with an underspecification account, in which the underspecified height values are [-high] and [-low]. MMN was larger for // as the deviant, but only when compared across conditions to itself as the standard. For the within-condition comparison, MMN was larger to /ɪ/ deviant minus // standard than to the reverse. A condition order effect was also observed. MMN amplitude was smaller to the deviant stimulus if it had previously served as the standard. In addition, the amplitudes of late discriminative negativity (LDN) showed similar asymmetry. LDN was larger for deviant // than deviant /ɪ/ when compared to themselves as the standard. These findings were compatible with an underspecification account, but also with other accounts, such as the Natural Referent Vowel model and a prototype model; we also suggest that non-linguistic factors need to be carefully considered as additional sources of speech processing asymmetries.